A micro study on centrifuge model test of dynamic compaction using discrete-element method. Issue 5 (30th October 2021) - Li, Yuqi; Zhang, Junhao; Chen, Jun; Chen, Xiaohui; Zhang, Wenjie
Abstract : Using the discrete-element method (DEM), a numerical simulation of dynamic compaction (DC) under an acceleration field of 50 g was used to study the microscopic behaviours and macroscopic responses of soils under DC on the basis of a centrifuge model test of DC. The crater depth of the numerical simulation was compared with that of the centrifuge model test and field test. The results showed that the crater depth of the numerical simulation was in reasonable agreement with that of the centrifuge model test and a field test. Microscopic behaviours and macroscopic responses of soils under DC can thus be simulated using DEM by applying a centrifugal force field. Variations of dynamic stress, porosity and coordination number under DC were analysed. The effect of local damping on crater depth was also assessed. This study sheds light on the microscopic mechanism of DC, which should be helpful for improving the effect of DC.